Shared decision-making in pediatric physical therapy: A qualitative study among adolescents, parents, and physical therapists - Selina Limmen; Dorinde L. Korteling; Manon A. T. Bloemen; Michiel A. J. Luijten; Marjolijn Ketelaar; Raoul H. H. Engelbert; Dirk T. Ubbink; Marij A. Hillen; Eugene A. A. Rameckers; Hedy A. van Oers; Lotte Haverman (PLoS ONE, 2026)
Objective Shared Decision Making (SDM) is a collaborative process between patients and clinicians. A structured approach for SDM in pediatric physical therapy is lacking. This two-phase study aimed to 1) explore how and when to apply SDM in pediatric physical therapy in primary healthcare, and to identify barriers and facilitators influencing its use, and 2) adapt an SDM model for use in pediatric physical therapy and propose strategies for implementation. Methods The study consisted of two phases. In Phase 1, six focus groups were conducted, two per participant group: adolescents (12-18y, n = 11), parents of children (4-18y, n = 9), and pediatric physical therapists (n = 6). A qualitative survey among 46 pediatric physical therapists validated focus group results. An inductive analysis explored how and when SDM should be applied, and a deductive analysis identified barriers and facilitators by linking codes to Consolidated Framework for Implementation Research (CFIR) domains. In Phase 2, the research team integrated results into an existing goal-based SDM-model, and implementation strategies were selected using the CFIR-Expert Recommendations for Implementing Change tool. Results SDM can begin at intake and goal setting, with ongoing, individualized involvement of children and parents throughout therapy. When comparing therapy options, treatment frequency, duration, homework, expectations, and possibilities at home can be discussed. Barriers included time constraints and the challenge of balancing multiple perspectives, while facilitators were the possibility to adapt SDM conversations per family and a supportive practice culture. A goal-based SDM-model was adapted for pediatric physical therapy. Implementation strategies identified were professional training, use of SDM tools, sufficient contact with parents, time to learn SDM, a supportive team culture, and empowering parents and children. Discussion This study provides guidelines for implementing SDM in pediatric physical therapy in primary care. A multifaceted implementation approach, guided by this study’s implementation strategies, may enhance SDM integration into clinical practice.